Improving the Monitoring of the Operational and Technical Condition of Rigid Airfield Pavements (Academic journal Industrial Machine Building Civil Engineering, 2022)
An analysis of domestic and foreign methods for assessing the operational and technical condition of airfield pavements is given. The essence of the ACN-PCN method for determining the bearing capacity of airfield pavements is described. It has been established that over a long period of the airfield pavement operation of the "Mykolayiv International Airport" under the natural influence, climatic and operational factors, destructions were formed on the pavement, which is distinctive for each type of artificial pavement of the runway, taxiway and apron. Based on the monitoring results, a forecast was made for the operational and technical condition of the rigid airfield pavements of the Mykolayiv International Airport.
Keywords: runway; apron; rigid airfield pavement; inspection, monitoring; operational and technical condition